Impact of the COVID-19 Pandemic on ACO Prevalence Among AECOPD Patients (2019-2023) and Clinical Characteristics by Blood Eosinophil Levels - Zhang S; Song W; Sun T; Wu S; Wang Z; Meng A (International Journal of COPD)
Siming Zhang, Wenhui Song, Tongxinwei Sun, Siyu Wu, Zheng Wang, Aihong Meng Department of Respiratory and Critical Care Medicine, Hebei Key Laboratory of Respiratory Critical Care Medicine, The Second Hospital of Hebei Medical University, Shijiazhuang, Hebei 050000, People’s Republic of ChinaCorrespondence: Aihong Meng, Department of Respiratory and Critical Care Medicine, Hebei Key Laboratory of Respiratory Critical Care Medicine, The Second Hospital of Hebei Medical University, No.215, Heping West Road, Shijiazhuang, Hebei, 050000, People’s Republic of China, Email mah123@hebmu.edu.cnPurpose: This study aimed to evaluate changes in the prevalence of Asthma-COPD Overlap (ACO) among patients with Acute Exacerbations of COPD (AECOPD) from 2019 to 2023. It also compared the clinical characteristics of patients across EOS thresholds (50, 150, and 300 cells/μL) to identify disease severity markers and guide individualized treatment strategies.Patients and Methods: Clinical data from AECOPD and ACO patients hospitalized at the Second Hospital of Hebei Medical University between January 2019 and December 2023 were analyzed. Patients were grouped by EOS levels (50, 150, and 300 cells/μL), and their clinical characteristics were compared.Results: Among 408 AECOPD and 275 ACO patients, the prevalence of ACO during the late pandemic period in 2023 was significantly higher than in the pre-pandemic period in 2019. ACO patients during the late pandemic period showed increased EOS counts and FeNO levels compared to pre-pandemic patients (P < 0.05). In AECOPD patients, those with EOS < 50 cells/μL had lower lymphocyte counts and higher NLR and FDP levels than other groups. Similarly, in ACO patients, the EOS < 50 cells/μL group showed lower lymphocyte counts and higher NLR levels. Patients with EOS ≥ 300 cells/μL were younger and exhibited higher FeNO levels than the EOS < 50 and 50– 150 cells/μL groups (P < 0.05).Conclusion: The prevalence of ACO among AECOPD patients increased during the late pandemic period, possibly indicating a role for type 2 inflammation. EOS thresholds of 50, 150, and 300 cells/μL may serve as markers of disease severity and aid in tailoring individualized treatment strategies.Keywords: type 2 inflammation, acute exacerbation of chronic obstructive pulmonary disease, asthma-COPD overlap, eosinophils, COVID-19 pandemic